Tip off the HAT- Epigenetic control of learning and memory by Drosophila Tip60. - Xu, S.; Elefant, F. (Fly, 2015)
Disruption of epigenetic gene control mechanisms involving histone acetylation in the brain causes cognitive impairment, a debilitating hallmark of most neurodegenerative disorders. Histone acetylation regulates cognitive gene expression via chromatin packaging control in neurons. Unfortunately, the histone acetyltransferases (HATs) that generate such neural epigenetic signatures and their mechanisms of action remain unclear. Our recent findings provide insight into this question by demonstrating that Tip60 HAT action is critical for morphology and function of the mushroom body (MB), the learning and memory center in the Drosophila brain. We show that Tip60 is robustly produced in MB Kenyon cells and extending axonal lobes and that targeted MB Tip60 HAT loss results in axonal outgrowth disruption. Functional consequences of loss and gain of Tip60 HAT levels in the MB are evidenced by defects in memory. Tip60 ChIP-Seq analysis reveals enrichment for genes that function in cognitive processes and accordingly, key genes representing these pathways are misregulated in the Tip60 HAT mutant fly brain. Remarkably, increasing levels of Tip60 in the MB rescues learning and memory deficits resulting from Alzheimer's disease associated amyloid precursor protein (APP) induced neurodegeneration. Our studies highlight the potential of HAT activators as a therapeutic option for cognitive disorders.